Self Control And Self Management Skills (SCSMk) in Patient with Diabetes Melitus - Rachmania, Diana; Taukhid, M.; Widayati, Dhina (Journal of Applied Nursing and Health, 2024)
Background: A person with Diabetes Mellitus is faced with various challenges in managing their health condition in order to prevent complications that can arise as a result of their disease. The patient's internal abilities are needed to prevent psychological deterioration which ends in various complications.  one of which is Self Control and Self Management Skills (SCSMk) which consists of three aspects, namely self-monitoring, self-evaluation and self-strengthening. This research aims to determine the Self Control and Self Management Skills of Diabetes Mellitus sufferers. Methods: The design of this research is quantitative descriptive. The research sample of 60 people suffering from diabetes mellitus was obtained using a purposive sampling technique taken from a population of 200 diabetes mellitus patients in the area. The instrument in this research is a questionnaire. Data were analyzed using descriptive percentage analysis. Results: Most respondents (73%) have Self Control and Self Management Skills (SCSMk) in the sufficient category Conclusion: Self monitoring is the dominant aspect possessed by respondents. When individuals have good self-monitoring, they can monitor the status and context of their own behavior such as their actions, thoughts and emotions. Respondents try to carry out positive behavior in the form of following instructions in managing diabetes mellitus treatment.